Kesesuaian Daya Dukung Lingkungan terhadap Mitigasi Kawasan Permukiman Kumuh di Perkotaan Banyuwangi - Setiawati, Hendri; Hidayati, Agustina Nurul; Rusdiyanto, Edi (Universitas Batanghari Jambi, 2025)
The purpose of this study is to analyze the suitability of environmental carrying capacity in slum areas in Banyuwangi City and to develop a mitigation concept for slum areas in Banyuwangi City. The method used is an overlay analysis of environmental carrying capacity to assess the suitability of environmental carrying capacity and the Analysis Hierarchy Process (AHP) to determine the priority of mitigation steps based on seven slum indicators. The results of the study showed that around 81% of slum areas in Banyuwangi City were assessed as being in accordance with environmental carrying capacity, while the other 19% were not in accordance in almost all villages with the largest area, namely Sobo Village.